(untitled) (Journal of Science and Technology, 2016)
A review of the distribution of crabs, lobster, shrimps and prawns found in Ghana revealed that crabs, shrimps and prawns are found in most regions of Ghana with abundant quantities in the Greater Accra, Central, Volta, Western and Eastern regions while lobsters are common in the regions along the coast. Compositional characteristics of the unprocessed mean and shells were found to be for Cardiosoma armatum, moisture 80.5%, protein 16.3%, chitin, 25.25%, for Callinectes latimanus, moisture, 86.7%, protein, 11.5%, chitin, 18.3%, for Panulirus regius, moisture, 80.1%, protein, 18.3%, chitin, 17.6%. The prawns Machrobrachium machrobrachion had a moisture of 71.1%, protein, 15.1%, chitin 20.0%, for Machrobrachuon Vollenhoven moisture, 69.7%, protein, 17.4%, chitin, 23.7% and for Panaeus noiialis, protein. 16.6%, moisture, 76.7%, and chain. 21.1%. All the types of crustacean meals had a low content of ash and fat, but rich quantities of calcium, iron, copper, and phosphorus were in limited quantities_ An important characteristic was the predominance of unsaturated fatty acids